FREQUENCY OF GASTRO ESOPHAGEAL VARICES IN CIRRHOTIC PATIENTS WITH SPLENOMEGALY - Dr Habibullah Jan; Dr Mustafa Kamal; Dr Muhammad Naeem; Nadin Salheya; Shivang Arvind Patel; Talmeez Zeb Shah; Fahmida Khatoon (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Cirrhosis of the liver, particularly in the presence of splenomegaly, is a known risk factor for the development of gastroesophageal varices (GEVs), which are one of the major causes of upper gastrointestinal bleeding. Understanding the frequency of GEVs in cirrhotic patients with splenomegaly can help prioritize screening and management strategies.Methods: A total of 225 cirrhotic patients with confirmed splenomegaly were included in this retrospective study. Endoscopic examination was performed to assess the presence and severity of GEVs. The study analyzed patient demographics, clinical characteristics, liver function tests, and splenic size measurements. The relationship between splenomegaly and the frequency of GEVs was evaluated using statistical methods.Results: Of the 225 patients, 68% had gastroesophageal varices, with 20% presenting with large varices, associated with higher risks of bleeding. A significant correlation was observed between the size of the spleen and the presence of GEVs (p < 0.05). Additionally, patients with advanced cirrhosis (Child-Pugh class C) had a higher prevalence of varices (80%), compared to those with compensated cirrhosis (56%, p < 0.01).Conclusion: This study confirms a high frequency of gastroesophageal varices in cirrhotic patients with splenomegaly, particularly those with advanced liver disease. The findings highlight the importance of screening for GEVs in these patients to prevent complications such as bleeding and rupture.